The essential theatre - Brockett, Oscar G.; Ball, Robert J. (Wadsworth Cengage Learning, 2014)
THE ESSENTIAL THEATRE will encourage you and get you excited about becoming an active theatergoer, while providing the insight and understanding that will enrich your theatre experience throughout your life.